Bimbingan Teknis Penyusunan Penelitian Tindakan Kelas dan Publikasi Ilmiah bagi Guru MI Al Ishlah Tiudan - Lilis Anifiah Zulfa; Rahmawati Mulyaningtyas (Abdimas Universal, 2022)
Writing scientific papers is important for the development of the teaching profession. One of the most popular scientific papers by the teachers is the results of classroom research or commonly known as CAR (classroom action research). CAR is useful for improving teacher performance and fixing problems in the classroom. CAR that has been prepared by the teacher has not been maximally published in the form of a journal. In fact, the results of this scientific publication can be used for the benefit of school accreditation and benefit of the public usage, especially the cognate teachers. Therefore, it is important to carry out technical guidance on the preparation of CAR and scientific publications for MI Al Ishlah Tiudan teachers. The method used in this research is Participatory Action Research method. The implementation of technical guidance for the preparation of CAR and scientific publications shows that the majority of teachers at MI Al Islah Tiudan Gondang have received guidance on the preparation of CAR, but there are still many who do not understand the actual CAR because the guidance only provides material. In this technical guidance activity, all participants seemed enthusiastic and had been able to prepare a good CAR draft. All participants are also ready to continue the development of their draft and prepare to publish it in a journal.